Experimentation of Two Types of Thermoelectric Modules for Converting Thermal Energy to Electricity - Miftah Almunir; Rifky (METALIK : Jurnal Manufaktur, Energi, Material Teknik, 2023)
Abstract Thermoelectric is a device that can convert heat energy (temperature difference) into electrical energy. Thermoelectric can work as an electric generator, heat pump, and as a coolant. This research is about two thermoelectric modules, namely the TEC 1-127061-12706 type and the TEG SP 1848. Generally, the TEC 1-12706 type module is used as a coolant, while the TEG SP 1848 type module is used as a generator. The purpose of this study was to obtain the performance of each of the second modules as a converter of thermal energy into electrical energy. This study uses an experimental method. From each type of module, four modules are assembled to form a system, in order to obtain two thermoelectric generator systems with different types of modules. The hot side of the module is attached to an aluminum plate and is given heat from the heat source from the heater. The cold side of the module is also aluminum affixed and provided with an ice cube cooler. In this study, ice cubes were used as a stabilizer for the cooling temperature. Data retrieval by measurement, namely the measurement of the temperature of the top aluminum, the temperature of the hot side, the temperature of the cold side, and the temperature of the bottom aluminum. connections and the resulting current of each thermoelectric system is measured to obtain its output power. The results showed that the thermoelectric generator type TEC 1-12706 produces a maximum electric power of 3,7908 W and a minimum of 0,9541. For the TEG SP 1848 type, it produces a maximum electric power of 5,7970 W and a minimum of 0,9250 W.